TIKA Rancang Bangun Rekomendasi Baca Buku Diperpustakaan Dengan Metode Apriorio - hasanah, tikatul hasanah (Universitas Muhammadiyah Riau, 2024)
Current technological advances make companies take advantage of them to simplify and advance their businesses. With the development of consumer purchasing power, players are required to implement better marketing strategies than their competitors. and likewise with the facilities at the school which provide a library for book borrowing transactions and to facilitate learning and knowledge for pupils and students. Libraries also play an important role as managers of developing information. The development of libraries is always related to information with manual libraries and digital libraries. Schools are a gathering place for students who are expected to maximize the potential of students reading existing books through technology that is currently developing. However, there are several problems that often occur regarding borrowing and selling books. There are many books with various book titles that are still difficult to find that have been in the library for a long time, but it takes a long time to find books that have been in the library for a long time. To overcome existing problems, there needs to be a system that can help make finding books easier. , and books that are of interest to students when visiting the library.